Controle e punição : a monitoração eletrônica em Minas Gerais - Rafaelle Lopes Souza (2019)
The purpose of this thesis is to understand the operation of electronic monitoring in its three situations of applicability in the state of Minas Gerais: pretrial detainees, a protective measure of urgency in cases of domestic violence and post-release supervision Electronic monitoring was officially implemented in Brazil from 2010, expanding its operations to almost all federal units by the end of 2017, reaching a total of 51,515 people monitored. The justification for implementing such a mechanism was centered on the prerogative of decreasing the prison population among pretrial detainees and convicted using the lowest cost without losing the power of state control. In this context, the present study was structured in two stages: the first exploratory phase sought to know all the functioning of electronic monitoring through observation of hearings and consultation in legislation on the subject, inquiries and lawsuits. The second stage aimed to understand the perception of the justice system operators and monitored the execution of electronic monitoring through interviews and questionnaires. Data from the perception survey with the monitored showed a greater emphasis on the punishment of electronic monitoring in their lives, while in the perception of the justice system the electronic monitoring acts as a rehabilitation factor in cases of criminal execution and domestic violence and in cases of measurement precautionary electronic monitoring is configured as a control mechanism much more as guarantor of procedural progress than control of crime.